2008
DOI: 10.1038/sj.jid.5701183
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Hair Follicle Immune Privilege Is Linked to Prevention of NK Cell Attack

Abstract: Hair follicles (HFs) enjoy a relative immune privilege (IP) that is characterized by downregulation of major histocompatibility complex (MHC) class I and local expression of potent immunosuppressants. Normally, natural killer (NK) cells attack cells with absent/low MHC class I expression. However, because few perifollicular NK cells are found around healthy human anagen HFs, we asked how HFs escape from NK cell attack. This study suggests that this happens via an active NK cell suppression. Alopecia areata (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
252
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(269 citation statements)
references
References 84 publications
11
252
0
6
Order By: Relevance
“…Several of these genes and pathways have a previously described role in AA pathogenesis, validating that our experimental approach is sufficiently sensitive to capture disease-relevant processes. 10,33 Although it has been shown that NK cells aggregate perifollicularly in AA lesional skin 3,4,34 and peripheral blood, 35,36 there is limited data regarding the role of NK cells in AA pathogenesis. Our data show an upregulation of NK-cell cytotoxicity in AA peripheral blood that, as suggested by others, 11,12,37 may promote the failure of hair follicle immune privilege.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these genes and pathways have a previously described role in AA pathogenesis, validating that our experimental approach is sufficiently sensitive to capture disease-relevant processes. 10,33 Although it has been shown that NK cells aggregate perifollicularly in AA lesional skin 3,4,34 and peripheral blood, 35,36 there is limited data regarding the role of NK cells in AA pathogenesis. Our data show an upregulation of NK-cell cytotoxicity in AA peripheral blood that, as suggested by others, 11,12,37 may promote the failure of hair follicle immune privilege.…”
Section: Resultsmentioning
confidence: 99%
“…NKG2D-expressing CD8 T cells infiltrate the surrounding HF in humans with AA. [3,4] We investigated whether MSCs inhibit CD8+NKG2D+ T-cell infiltration in AA skin lesions. The CD8+NKG2D+ T cells were less observed in MSCtreated skin lesions than in control skin ( Figure 2B, Table S2a).…”
Section: Resultsmentioning
confidence: 99%
“…[1] Th1 cytokines and chemokines, such as interferon (IFN)G, CXCL9 and CXCL10, are predominantly detected in AA lesions and might induce the collapse of the hair follicle immune privilege. [2,3] Recent studies have shown that a NK cell receptor, NKG2D-mediated signalling, has been strongly associated with the pathogenesis of AA. [4] The antibody-mediated blockade of IFNG prevented AA development in grafted mice and blocked the accumulation of CD8+NKG2D+ T cells in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…An unknown trigger may possibly be a signal to destroy eHFSCs which would eliminate hair follicle ability to regenerate and self-repair and at the same time to stimulate all other clinical and histopathological features of the disease. [19][20][21][22] The theory of the immune attack on eHFSCs is crucial for the etiology of cicatricial alopecia. MHC class I, ÎČ2-macroglobulin and MHC class II are subjected to different regulation within a hair bulb in the various cicatricial alopecia units compared to those in the not affected skin.…”
Section: Etiology Of Cicatricial Alopeciamentioning
confidence: 99%